2009
DOI: 10.1021/jo8022523
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium(I)-Catalyzed Synthesis of Indoles: Amino-Claisen Rearrangement of N-Propargylanilines

Abstract: Mild and facile preparations of 2-substituted or 2,3-disubstituted indole compounds were achieved by RhH(CO)(Ph(3)P)(3) (4-10 mol %)-catalyzed reaction of N-propargylanilines in hexafluoroisopropyl alcohol (HFIP). The formation of indoles was proven to be derived from an o-allenylaniline intermediate, which was generated by the Rh(I)-catalyzed amino-Claisen rearrangement of N-propargylanilines. The catalytic system is also available for the one-pot synthesis of indoles by reacting N-alkylaniline (1 equiv) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 87 publications
0
24
0
1
Order By: Relevance
“…The reaction could be combined with in situ synthesis of propargyl amines, extending the sequence to a trio. [67] For example, treatment of a pre-mixed solution of bromobutyne and aniline with rhodium catalyst in the presence of base and phosphine at reflux in hexafluoroisopropyl alcohol (HFIP) produced indole 208 in good yield.…”
Section: [33]-sigmatropic Rearrangementsmentioning
confidence: 99%
“…The reaction could be combined with in situ synthesis of propargyl amines, extending the sequence to a trio. [67] For example, treatment of a pre-mixed solution of bromobutyne and aniline with rhodium catalyst in the presence of base and phosphine at reflux in hexafluoroisopropyl alcohol (HFIP) produced indole 208 in good yield.…”
Section: [33]-sigmatropic Rearrangementsmentioning
confidence: 99%
“…Akio Saito and Yuji Hanazawa of Showa Pharmaceutical University published 22 a full account of the Rh-mediated cyclization of propargylaniline derivatives, such as 44 (Scheme 16) that they developed. This reaction is apparently proceeding via rearrangement to an intermediate o -allenylaniline, that then cyclizes to the product, 45 .…”
Section: Typementioning
confidence: 99%
“…Saito and Hanzawa extended their cycloisomerization route, involving the aminoClaisen rearrangement-cyclization cascade reaction (Scheme 9.68), to a one-pot procedure toward the functionalized 2,3-dimethylindole derivatives 281 (Scheme 9.97) [226]. The key propargyl anilines 280 were generated in situ via the propargylation of substituted anilines 278 with the propargyl bromide 279.…”
Section: Synthesis Of Indoles Via Intramolecular Arylation Reactionsmentioning
confidence: 99%
“…, n-Bu, n-Pr, 1-cyclohexenyl R 1 = Ph, p-Tol, p-F-C 6 H 4 -, p-MeO-C a]indole core 187 could be accessed via the W(0)-catalyzed ring closure of C,N-divinyl-substituted imines 185 (Scheme 9.67)[224].More recently, Saito and Hanzawa demonstrated that a variety of fused, tri-, tetraand penta-substituted indoles 190 could be efficiently accessed via the Rh(I)-catalyzed cycloisomerization of N-propargyl anilines 188 (Scheme 9.68)[225,226]. This transformation presumably involves the initial Rh(I)-catalyzed amino-Claisen rearrangement of 188 to produce a putative reactive allenyl aniline intermediate 189, which is smoothly converted into the indole core, as exemplified by the cycloisomerization of an independently prepared allene 191 (Scheme 9.69).…”
mentioning
confidence: 99%